2004
DOI: 10.1128/mcb.24.20.8963-8969.2004
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase II Carboxy-Terminal Domain Phosphorylation Is Required for Cotranscriptional Pre-mRNA Splicing and 3′-End Formation

Abstract: We investigated the role of RNA polymerase II (pol II) carboxy-terminal domain (CTD) phosphorylation in pre-mRNA processing coupled and uncoupled from transcription in Xenopus oocytes. Inhibition of CTD phosphorylation by the kinase inhibitors 5,6-dichloro-1␤-D-ribofuranosyl-benzimidazole and H8 blocked transcription-coupled splicing and poly(A) site cleavage. These experiments suggest that pol II CTD phosphorylation is required for efficient pre-mRNA splicing and 3-end formation in vivo. In contrast, processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 44 publications
4
81
1
1
Order By: Relevance
“…Recent studies have demonstrated that TFIIH is a rate-limiting factor during the elongation phase of β-globin gene expression (28,29), and this is consistent with the fact that patients with mutations in TFIIH suffer from β-thalassemia (30). Together, these studies indicate that TFIIH plays a crucial role in β-globin gene expression.…”
Section: Resultssupporting
confidence: 71%
“…Recent studies have demonstrated that TFIIH is a rate-limiting factor during the elongation phase of β-globin gene expression (28,29), and this is consistent with the fact that patients with mutations in TFIIH suffer from β-thalassemia (30). Together, these studies indicate that TFIIH plays a crucial role in β-globin gene expression.…”
Section: Resultssupporting
confidence: 71%
“…Inhibitors of Cdk9 cause elongational arrest and can disrupt cleavage/polyadenylation 38,39 , but it is not clear how they affect recruitment of 3′ end processing factors. We investigated how DRB affects pol II, CstF and CPSF localization.…”
Section: Co-localization Of 3′ Processing Factors and Pol II At 5′ Anmentioning
confidence: 99%
“…CTD S2 phosphorylation is usually regarded as a signature of elongating pol II within a gene 5, 7 however our results suggest a role for this modification well downstream of the gene where 3′ processing factors are recruited. How DRB inhibits cleavage/polyadenylation 38,39 is not completely resolved, but it correlates with both reduced recruitment of CstF and CPSF in 3′ flanking regions and inhibition of 3′ pausing (Figs. 6B, C, Supplementary Table 2).…”
Section: Pausing Termination and Recruitment Of 3′ End Processing Fmentioning
confidence: 99%
“…First, transcription may target RNA to splicing, ensuring that transcribed introns will be recognized, committed to the splicing pathway, and removed, resulting in an improved overall efficiency of splicing. Such an effect has been observed in vivo, where splicing of a synthetic RNA injected into X. laevis oocytes was less efficient than cotranscriptional processing (Bird et al 2004). Second, splicing kinetics may be improved, if the transcription elongation complex delivers some or all components of the spliceosome to splicing signals; this could reduce the time needed for splicing complex formation and speed up all the steps of the process that precede the catalytic steps.…”
Section: Introductionmentioning
confidence: 99%